# 2009 AIME I Problems/Problem 8

(diff) ← Older revision | Latest revision (diff) | Newer revision → (diff)

## Problem

Let $S = \{2^0,2^1,2^2,\ldots,2^{10}\}$. Consider all possible positive differences of pairs of elements of $S$. Let $N$ be the sum of all of these differences. Find the remainder when $N$ is divided by $1000$.

## Solution 1 (Extreme bash)

Find the positive differences in all $55$ pairs and you will get $\boxed{398}$. (This is not recommended unless you can't find any other solutions to this problem)

## Solution 2 (bash)

When computing $N$, the number $2^x$ will be added $x$ times (for terms $2^x-2^0$, $2^x-2^1$, ..., $2^x - 2^{x-1}$), and subtracted $10-x$ times. Hence $N$ can be computed as $N=10\cdot 2^{10} + 8\cdot 2^9 + 6\cdot 2^8 + \cdots - 8\cdot 2^1 - 10\cdot 2^0$. Evaluating $N \bmod {1000}$ yields: \begin{align*} N & = 10(2^{10}-1) + 8(2^9 - 2^1) + 6(2^8-2^2) + 4(2^7-2^3) + 2(2^6-2^4) \\ & = 10(1023) + 8(510) + 6(252) + 4(120) + 2(48) \\ & = 10(1000+23) + 8(500+10) + 6(250+2) + 480 + 96 \\ & \equiv (0 + 230) + (0 + 80) + (500 + 12) + 480 + 96 \\ & \equiv \boxed{398} \end{align*}

## Solution 3

This solution can be generalized to apply when $10$ is replaced by other positive integers.

Extending from Solution 2, we get that the sum $N$ of all possible differences of pairs of elements in $S$ when $S = \{2^0,2^1,2^2,\ldots,2^{n}\}$ is equal to $\sum_{x=0}^{n} (2x-n) 2^x$. Let $A = \sum_{x=0}^{n} x2^x$, $B=\sum_{x=0}^{n} 2^x$. Then $N=2A - nB$.

For $n = 10$, $B = 2^{11}-1 = 2047 \equiv 47 \pmod{1000}$ by the geometric sequence formula. $2A = \sum_{x=1}^{n+1} (x-1)2^x$, so $2A - A = A = n2^{n+1} - \sum_{x=1}^{n} 2^x$. Hence, for $n = 10$, $A = 10 \cdot 2^{11} - 2^{11} + 2 = 9 \cdot 2^{11} + 2 \equiv 48 \cdot 9 + 2 =$ $434 \pmod{1000}$, by the geometric sequence formula and the fact that $2^{10} = 1024 \equiv 24 \pmod{1000}$.

Thus, for $n = 10$, $N = 2A - 10B \equiv 2\cdot 434 - 10\cdot 47 = 868 - 470 = \boxed{398}$.

## Solution 4

Consider the unique differences $2^{a + n} - 2^a$. Simple casework yields a sum of $\sum_{n = 1}^{10}(2^n - 1)(2^{11 - n} - 1) = \sum_{n = 1}^{10}2^{11} + 1 - 2^n - 2^{11 - n} = 10\cdot2^{11} + 10 - 2(2 + 2^2 + \cdots + 2^{10})$ $= 10\cdot2^{11} + 10 - 2^2(2^{10} - 1)\equiv480 + 10 - 4\cdot23\equiv\boxed{398}\pmod{1000}$. This method generalizes nicely as well.

## Video Solution

The problems on this page are copyrighted by the Mathematical Association of America's American Mathematics Competitions. 